Efeito Aharonov-Casher em potenciais centrais - Barboza, Priscila Mayana Torres (2018)
In this work, we investigate the system in which a neutral particle with magnetic dipole momentum interacts with an external electric ﬁeld subject to the central potentials, such as scalar potentials proportional to the radial distance and Coulomb like potential. In addition, we analyse the same system when it is conﬁned to a two-dimensional quantum ring and to a quantum dot. In the search for analytical solutions for the Schrödinger-Pauli equation we show that the energy states for this system of a neutral particle subject to the central potentials depend on the quantum geometric phase φAC and the quantum numbers associated with the radial modes, angular momentum, and spin of the system {n, l, s}. Furthermore, we present the quantization of Landau for a neutral particle with a permanent magnetic dipole moment in the presence of external ﬁelds and under the inﬂuence of a Coulomb like potential. We use the idea of Ericsson e Sjöqvist which consists in using the system proposed by Aharonov and Casher to generate an analogue of the quantization of Landau for neutral atom systems. Moreover, we observe that when the analogue of the Landau quantization is subject to a Coulomb like potential its cyclotron frequency is modiﬁed in contrast with the behavior found by of reference. Finally, we discuss the quantum eﬀect characterized by the dependence of quantum numbers with the angular frequency.